Claude Ake – Democracy and Development in Africa: A Review and a Tribute - Ukor, Venatius Azinor; Obo, Ugumanim Bassey (Journal of Central and Eastern European African Studies, 2026)
This paper which takes the form of a review and a tribute is an acknowledgement of the gargantuan contributions of Professor Ake – one of Africa’s most iconic and venerable thinkers – to the development of radical and revolutionary social science scholarship. A globally renowned Political Scientist whose intellectual compass traversed every area of social science, Ake believed in the transformational power of scientific knowledge and broadened its horizons through his many publications. Whereas it is not an assessment of Professor Ake’s works, this essay reinforces the immortal stature of a man who challenged an unjust status quo and widened the frontiers of progressive scholarship through his numerous research. This essay specifically examines Democracy and Development in Africa (1996), one of Ake’s last works whose analysis is on the nexus between democracy and development in Africa. The book x-rays the problem of leadership failure in Africa and highlights the anti – democratic and anti – development tendencies of African elites. This paper concludes that Professor Claude Ake was one of Africa’s great gifts to humanity, and the book under review is strongly recommended to students, researchers and policy makers interested in democratic governance and development – especially in Africa and the Third World.